Energy and nutrient production in Ethiopia, 2011-2015: Implications to supporting healthy diets and food systems - Baye, K.; Hirvonen, Kalle; Dereje, M.; Remans, R. (Public Library of Science, 2019)
Agricultural sector plays a key role towards achieving healthier diets that are deemed critical for improving health and nutritional outcomes. To what extent the current food supply systems support healthy diets remains unknown. Using annual and nationally representative data on crop and livestock production in Ethiopia, we assess the national agricultural sector from a nutrition lens and its role in supporting healthy diets in the country. We do so by converting the agricultural production into energy and nutrients for the period of 2011–2015. These data show that the national food production has increased dramatically over the 5-year period to supply more than 3,000 calories per capita in 2015. Moreover, nutrient production gaps have substantially decreased (2011–15), but deficits in energy (5%), vitamin C (16%), and calcium (9%) production remained in 2015. However, this production growth–coming primarily from the cereal sector and at the expense of other food groups–led to a decrease in production diversity as reflected by a drop in the Shannon index between 2011 and 2015. Together these findings imply that the production increases in Ethiopia would need to be sustained to feed the rapidly growing population but more emphasis should be given to diversification to support healthy and nutritionally diversified diets.